Potential Anticholesterol Infusion of Malaca Leaf (Phyllanthus Emblica) In Mice (Mus Musculus) Hypercholesterolemia - Asmilia, Nuzul; Silvana, Sartika; TR, T. Armansyah; Rasmaidar, Rasmaidar; Isa, M (Jurnal Sain Veteriner, 2025)
The aim of this research was to find out infusion test of malaka leaves (Phyllantus emblica) to mice (Mus musculus) blood cholesterol rate which hypercholesterolemic mice. Twenty male mice with the age of 3 month and clinically healthy were used in this research. All mice were randomly divided into 4 treatment groups, 5 mice each. K1 was negative control group. K2 was positif control group, fed with hypercholesterolemic feed. K3 and K4 group were fed with hypercholesterolemic feed and infusion of malaka leaves with the doses of 0,04 and 0,08 mg body weight respectively. The result of statistic analysis showed that infusion of malaka leaves significantly effect (P<0,01) on the decrease of cholesterol level of male mice inducedby hypercholesterolemic feed. The treatment of infusion of malaka leaves 0,04 mg and 0,08 mg was able to decrease the cholesterol level ofmice induced by hypercholesterolemic feed. The advance test showed that the treatment K1 significantly effect (P<0,01) compare to K2 and K3. The K2 treatment significantly effect (P<0,01) with K1, K3, and K4. The K3 treatment showed no significanly effect compare to K4 (P<0,05). In conclusion, the administration of infusion of malaka leaves with the dose of 0,04 and 0,08 mg reduce cholesterol level.